Idiomatic Expression in The American Sitcom Series “Fresh Off The Boat” Directed By Nahnatchka Khan - Ayunda Permatasari; Yesika Maya Ocktarani; Yulia Mutmainnah (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
This research aims to classify the form and meaning of idiomatic expressions in the American Sitcom entitled “Fresh Off the Boat”. This research focus on seasons 5 and 6 that released on 2019 and 2020. The data of this research is in the form of utterances which contains idiomatic expressions uttered by three main characters, Eddie Huang, Louis Huang, and Jessica Huang. The researcher uses descriptive qualitative method to analyze the research finding. From those series, there are 93 idiomatic expressions based on theory proposed by Adam Makkai, they are 21 Phrasal Verb Idioms, 50 Tournure Idioms, 1 Irreversible Binomial Idiom, 18 Phrasal Compound Idioms, and 3 Incorporating Verb Idioms. From those data, the researcher compares the lexical and contextual meaning of idiomatic expressions in the utterances. Based on the research’s finding, several idiomatic expressions have the same lexical and contextual meaning. However, the contextual meaning dominated the meaning of idiomatic expressions in this series because an idiomatic expression cannot be seen lexically or based on the dictionary meaning. It should be seen based on the context of the idiomatic expression is used because sometimes, it carried figurative meaning. Keywords: idiom; form of idiomatic expressions; meaning of idiomatic expression.